HIV Testing and Health Care Utilization Behaviors Among Men in the United States: A Latent Class Analysis. (May 2017) - Dangerfield, Derek T.; Craddock, Jaih B.; Bruce, Omar J.; Gilreath, Tamika D.
Abstract : N/A: Emphasis has been placed on HIV testing and health care engagement, but little is known about how testing and engagement intersect, especially for men. We used latent class analysis to explore underlying profiles of U.S. men regarding HIV testing and health care utilization using data from the 2014 National Health Interview Survey. Multinomial regression was used to predict class membership in four classes: (a) Low HIV Testing/No Health Care Utilization, (b) Some HIV Testing/Low Health Care Utilization, (c) No HIV Testing/Some Health Care Utilization, and (d) High HIV Testing/High Health Care Utilization. Most men were in the No HIV Testing/Some Health Care Utilization class (46%), with a 0% chance of ever having had an HIV test but an 89% chance of seeing a general practitioner in the previous year. Research should include qualitative measures to capture information on facilitators and barriers to HIV testing for men who see general practitioners.